Six domains of health: a practical approach to identifying priorities in dementia care - Sadak, Tatiana; Borson, Soo (Frontiers in Dementia, 2023)
Background High-quality healthcare for people living with dementia encompasses both patients and care partners (CPs). A framework populated with simple assessment tools is needed to deconstruct this complexity into actionable domains that inform assessment and care planning for individuals and dyads, help differentiate care team roles, and can more fully estimate true population burden in health and social care systems. Design Researchers used a cross-sectional mixed-methods descriptive study to illustrate the use of an inductive Six Domain framework and simple assessment tools in a sample of dyads selected for complexity. Setting Data was collected from three university-affiliated hospitals with a shared electronic medical record (EMR). Participants Eighty-eight CPs for people living with dementia (care recipients) newly discharged home after an acute medical hospitalization participated. Measures Care recipients' outpatient and inpatient diagnoses, medications, and care were extracted from the EMR. CPs completed an in-home semi-structured interview and study measures. Data were sorted into six domains: three care recipient-focused domains (cognition, emotion/behavior, general and functional health); a single CP-focused domain (mood, cognition, stress, and self-rated health); a health-related social needs domain (enrollment of persons with dementia in low-income insurance, CP-reported financial strain); and a care delivery domain (CP-reported engagement with clinicians in care recipients' care planning, and match between CP-reported knowledge of care recipients' medical care needs and medical records). Results As expected, all people living with dementia had significant cognitive, neurobehavioral, and medical complexity requiring extensive oversight and management at home. Over a third of CPs reported high stress, depression, or anxiety. A fifth screened positive for one or more indicators of poor health, cognitive impairment, and/or health-related social needs. CP reports and care recipients' medical records were discordant for chronic conditions in 68% of cases and for prescribed medications in 44%. In 85% of cases, there were gaps in indicators of CP-clinician collaboration in care management. Conclusion and relevance The Six Domains of Health framework captures a broad array of challenges that are relevant to providing comprehensive dyadic care and setting individualized health and social care priorities. With further study, it could provide conceptual scaffolding for comparative population research and more equitable, fully integrated pathways for care.